The role of internal balancing in response to China's military rise in the Asia-Pacific : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy at Massey University, Manawatū, New Zealand - Amerian, Sirous (Massey University, 2022)
In Asia, alongside the increased power and threat of China as a rising power, the era of external balancing/alliance building and relying on the US is on the decline, and it is expected that states take care of their own security needs. Consequently, more states should rely on their internal and military capacities to balance against potential threats. A vast amount of realist literature has employed various theories in predicting state behaviour against powerful rivals and threats. Most such studies conclude with alliance building as their primary prescription and don’t pay much attention to internal balancing. Yet, with the points illustrated previously, this study believes external balancing alone is not enough. With the US leaving, there will be a security vacuum and countries need to take care of themselves. In a more recent iteration of neo-classical realism, the Dynamic Balancing model by Kai He and one of its hypotheses suggests that in a Uni-polar world, the current prevailing structure of the world we live in, if threats come from non-hegemonic states, the threatened states could seek help or ally with the hegemon. Still, such relations with the hegemon would be closer to bandwagoning rather than alliance building. Even if forged, this alliance would not last. Therefore, in a unipolar system, the primary strategy of non-hegemon states, the cases being studied here, would be internal balancing. This study, by employing qualitative document analysis resources, wants to investigate and test this hypothesis further by looking at middle powers, as significant players and military spenders in the region and countries that enjoy deep security and economic relations with the US, and investigate how they have approached internal balancing, specifically its military side to balance against China, and if the hypothesis suggested in this model is correct. The contribution of this study would be its attempt to study and test the Dynamic Balancing model and see how each case has performed in relation to the hypothesis.
Keywords: dynamic balancing; internal balancing; South Korea; Australia; India; rise of China; 440804 Defence studies